COMPARATIVE OUTCOMES OF EARLY VERSUS DELAYED WOUND GRAFTING IN BURN PATIENTS: A SYSTEMATIC REVIEW AND META-ANALYSIS - Bunga, Rafeni; Nata'admaja, Beta Subakti (Universitas Airlangga, 2025)
Highlights: Early wound grafting appears to improve hospital stay duration and functional recovery. There is a tendency of higher graft success rates and reduced infection risks compared to delayed grafting in burn patients. Abstract: Introductions: Burns are a significant global health issue, with over 265 million cases annually. Effective burn wound treatment is crucial, and the timing of surgical skin grafting plays a key role in recovery. Early excision and grafting, typically within 48 hours, is standard practice as it reduces morbidity, mortality, infection, graft failure, and hospitalization. Delaying grafting increases infection risk, while early intervention has been shown to improve wound healing. However, challenges like poor resuscitation and resource limitations may hinder early grafting, particularly in low-resource settings. This review evaluates the evidence on optimal grafting timing in burn patients. Methods: A systematic review and meta-analysis were conducted. A literature search was conducted from July 2024 to January 2025 comparing early (within 3-7 days) versus delayed (after 7 days) grafting. Studies included randomized controlled trials, cohort studies, and observational studies, with outcomes focused on hospitalization duration, infection rates, blood loss, and limb functionality. Results: Of 250 studies identified, seven met eligibility criteria. Early grafting significantly reduced hospital stay by 8.89 days (95% CI: -12.88 to -4.89) compared to delayed grafting. No significant differences were observed between early and delayed grafting in terms of blood loss, infection rates, or post-operative grip strength. However, early grafting resulted in better post-operative Total Active Movement (TAM) scores (MD: 22.10 [95% CI: 17.95 to 26.24]). Conclusion: Early grafting improves hospital recovery and functional outcomes. Further research is needed to confirm these findings.